Air Pollution Control Equipment Selection Guide - Schifftner, Kenneth C (CRC Press, 2009)
The selection of air pollution control apparatus can be a daunting task even for experienced pollution control professionals. The Air Pollution Control Equipment Selection Guide eases the burden by providing extensive information on the best equipment available for any air pollution control problem. Instead of endorsing one technology over another, the author provides general information so that you can decide on the proper technology to use for any given application.